Research and design - Seivewright, Simon (Lausanne : AVA Academia, 2007)
"This book will lead you through the essential stages of research and translation into design ideas. It discusses elements such as the brief and the constraints it can place on the research and design process, and explains the importance of identifying your target market and understanding the different levels and genres of fashion before setting out on the creative research. The book then explores the many avenues for researching, the need to set a theme, concept or narrative to your collection and explains how to translate research into early design ideas and techniques used in bridging the gap between research and design. Design development is also explained and communicated through a series of structured stages. Finally the book shows and explores a variety of approaches to communicating and rendering your design work."--Publisher.
Includes bibliographical references (p. 164-167).
Keywords: Fashion design